2011
DOI: 10.1155/2011/726405
|View full text |Cite
|
Sign up to set email alerts
|

Enteromorpha compressa Exhibits Potent Antioxidant Activity

Abstract: The green macroalgae, Enteromorpha compressa (Linnaeus) Nees, Ulva lactuca, and E. linza, were seasonally collected from Abu Qir bay at Alexandria (Mediterranean Sea) This work aimed to investigate the seasonal environmental conditions, controlling the green algal growth, predominance, or disappearance and determining antioxidant activity. The freshly collected selected alga (E. compressa) was subjected to pigment analysis (chlorophyll and carotenoids) essential oil and antioxidant enzyme determination (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 20 publications
8
40
0
Order By: Relevance
“…The recorded activity was shown to correlate with the total phenolic content in the algal extracts. In most algae, phenols are important anti oxidants because of their ability to scavenge free radicals such as singlet oxygen, superoxide and hydroxyl radicals [24]. Like our results, numerous studies have found a high correlation between antioxidative activities of algae and phenolic content [14,25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The recorded activity was shown to correlate with the total phenolic content in the algal extracts. In most algae, phenols are important anti oxidants because of their ability to scavenge free radicals such as singlet oxygen, superoxide and hydroxyl radicals [24]. Like our results, numerous studies have found a high correlation between antioxidative activities of algae and phenolic content [14,25].…”
Section: Discussionsupporting
confidence: 85%
“…Previous antioxidant activity for different Cystoseira species, using other extraction solvents; the antioxidant activity studies have demonstrated was confirmed by acetone algal extracts. Different extraction solvents, according to the their polarity, may extract various compounds including pigments (chlorophylls a, b, carotenoids), alkaloids, and phenolic compounds, as well as essential oil which can participate in the great antioxidant activity [24]. This means that synergistic effects may occur between these constituents leading to the pronounced antioxidant activity of algal extracts (containing the antioxidant active components).…”
Section: Discussionmentioning
confidence: 99%
“…There is a current worldwide interest in finding new and safe antioxidants from natural sources such as plant material to prevent oxidative deterioration of food and to minimize oxidative damage to living cells The use of synthetic antioxidants has decreased due to their suspected activity as promoters of carcinogenesis as well as a general consumer rejection of synthetic food additives [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are widely distributed natural compounds and also the most important natural phenolics. In most lichens, phenols are important antioxidants because of their ability to scavenge free radicals such as singlet oxygen, superoxide and hydroxyl radicals (Shanab et al 2011). Numerous researches reported a significant correlation between antioxidative activities of lichens and phenolic content (Behera et al 2009;Ranković et al 2012).…”
Section: Resultsmentioning
confidence: 99%